HYDRODEOXYGENATION OF METHYL OLEATE INTO DIESEL-LIKE HYDROCARBONS OVERPd/SBA-15 CATALYSTS - LEE, SIEW PEI (2013)
Hydrodeoxygenation of vegetable oil has a potential to be converted into renewable and carbon-neutral fuel-like hydrocarbons. This present study focuses on generation of diesel range of hydrocarbons (C15 - Cig) from hydrodeoxygenation of 70% technical grade of methyl oleate over the in-house fabricated Pd/SBA-15 using autoclave reactor. Two different morphologies of well-ordered hexagonal structure SBA-15 were synthesized, that were necklace-like and rod-like structures. The morphologies and physiochemical properties of the products were found to be greatly affected by the shearing stress exerted in the synthesis mixture. Necklace-like SBA- 15 comprised of a bundle of individual rodlike silicas units provided larger surface area than rod-like SBA-15.